Analisis Teknik Dan Perancangan Alat Manual Pengepres Kaleng Minuman Bekas Di Pengepul Rongsokan dengan Metode Stakeholder, Holistik, Interdisipliner dan Partisipatori (SHIP) - Basuki Rahayu; Roberta Zulfhi Surya; Asniati Bindas (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
The role of reduce, reuse and recycle is directly played by used goods collectors and scavengers in reducing the volume of waste. Used cans collected by scavengers will usually be re-cycled, namely the processing of new cans and handy craft. But often used cans at collectors do not meet the standards for goods to be recycled, such as damaged forms and storing a lot of dirty materials such as sand, soil and rust. The selling price of used press cans with irregular shapes is IDR 25,000 while cans with clean quality sell for IDR 35,000. The criteria for clean quality cans are pressing cans neatly and not containing any impurities. This research attempts to design a press tool that is tailored to the participation of stakeholders and is discussed in an interdisciplinary manner as a whole so that it is expected to provide results that can be beneficial to science and people's welfare. The results of this study are that the pressing time of cans tends to be the same and there is even an increase in the average pressing time of 0.39 minutes. but the results obtained from the new tool have increased even though the pressing time is the same after the redesign of the press system can press and the level of satisfaction with the can press has increased by 16% due to neat results, selling prices have increased and injury has been avoided